Preliminary study of cultivated algae from South Sulawesi as antibacterial agent against fish pathogenic bacteria. Issue 1 (September 2020) - Zainuddin, EN; Tassakka, ACM; Manggau, M; Syamsuddin, R
Abstract: The way to prevent or treating bacterial diseases outbreaks with drugs or chemicals is the one of main solutions to solve the problems in aquaculture. The use of antibacterial agents has increased significantly in aquaculture practices, since the antibiotics used in both human as well as veterinary medicines have been tried experimentally to treat bacterial infections of fish. However, the evolving resistance of fish pathogenic bacteria to existing antibiotics has necessitated development of new alternatives. In the last three decades the discovery of metabolites with biological activities from algae has increased significantly. In this study, sixteen extracts from four algae of genus Eucheuma were tested by in-vitro against five pathogenic bacteria ( Aeromonas salmonicida, Aeromonas hydrophila, Pseudomonas anguilliseptica, Vibrio anguillarum and Yersinia ruckeri ). The algae were extracted in Soxhlet apparatus using solvents with increased polarity (hexane, dichloromethane, methanol and water) for 24 h. The extract solutions were then evaporated and liophilized before using for the antibacterial test with agar diffusion method. The results revealed that three of four extracts (hexane, dichloromethane and water) were active against all pathogens, while methanol did not. The highest activity was shown by water extract, followed by the hexane and the dichloromethane extracts with lower activities. The water extract of Eucheuma spinosum had a broad activity since it was active against four of five pathogenic strains. Vibrio anguillarum and Pseudomonas anguillaseptica were the two most susceptible pathogens, while the most resistant was presented by Aeromonas hydrophila . The screening results confirm that algae were potential to be developed as a source of antibacterial compounds or as a health-promoting food for aquaculture.